Sport Participation and Academic Achievement: Is There a Plateau Effect? - Hanson, Lindsay; Kent, Aubrey (My University, 2002)
The purpose of this study was to investigate the relationship between athletic participation and academic performance in Florida high school students; and more specifically, to determine if there was an optimal level in terms of time spent participating in organized sports and increased performance in the classroom. Possible differences between men and women were also investigated. By investigating various levels of athletic involvement, this research attempted to determine the most productive level of participation. One hundred sixty seven high school students were categorized into four involvement levels (low, medium, high, elite) based on the number of hour each student participated in sport each week. The results showed that there was an optimal level of athletic participation in terms of increased grade point average. Those athletes involved in moderate to high levels had significantly higher grade point averages than did those engaged at a "low" level. Further, a plateau effect was evident as grade point average scores did not significantly decrease after the optimal point. It is interesting to point out that female performance decreased from the "high" to "elite" level while male performance continued to increase. This may be due in part to a restriction in range, given that the female GPA's were already high, and thus were constrained from rising further.
Keywords: academic performance high school; identity